Efficacy and safety of hyperbaric oxygen therapy for moderate-to-severe ulcerative colitis: a protocol for a systematic review and meta-analysis - Lihong Luo; Lei Qing; Chengjiao Yao; Dongying Liu; Yilin Li; Tinglin Li; Peimin Feng (BMJ Open)
Introduction Ulcerative colitis (UC) is a type of inflammatory bowel disease, and 62% of patients with UC felt that it is difficult for them to live a normal life. Furthermore, some researches have shown that about 15% of patients with UC undergo at least one extreme clinical course in their lifetime, and 10%–30% of patients with UC oblige colectomy. Although many investigations have demonstrated that HBO2 has a beneficial impact on UC treatment, a systematic review and meta-analysis are unavailable. Therefore, a meta-analysis is essential to assess the efficacy and safety of HBO2 in treating UC.Methods and analysis A systematic search plan will be performed in the following seven databases with a restriction of time from inception to September 2020 to filter the eligible studies: PubMed, Web of Science, Embase, Cochrane Library, China National Knowledge Infrastructure, Chinese Scientific Journal Database (VIP) and Chinese Biomedical Database WanFang. Other related resources will be also searched. Two independent reviewers will choose eligible researches and extract data. The risk of bias will be evaluated based on Cochrane Collaboration’s Risk of Bias tool and Newcastle-Ottawa Scale. Eventually, a systematic review and meta-analysis will be performed via the Review Manager V.5.3 statistical software and STATA V.14.0 software.Ethics and dissemination This study will not involve the individual patient and any ethical problems since its outcomes are based on published data. Therefore, no ethical review and approval are required. We plan to publish the study in a peer-reviewed journal.PROSPERO registration number CRD42020210244.